Does Monopoly Promote Innovation? A Theoretical Vindication of the Schumpeterian Hypotesis - Vincenzo Denicolo'; Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
In this paper we reconsider the well known Schumpeterian hypotesis stating the superiority of monopoly over competition in generating fast technological progress. This hypotesis has been challenged by Arrow (1962) and Dasgupta and Stiglitz (1980), who have shown that a monopolist has lower incentives to innovate. After reassessing arrow's and Dasgupta and Stiglitz's argumet, we show that their conclusion can be reserved and the Schumpeterian conjecture can be confirmed. More precisely, if by "competitive industry" we mean a large Cournot market, then, for small innovations, we show that a monopolist invests in R&D more than such an industry.
Keywords: 330